Management of Recalcitrant Carpal Tunnel Syndrome. Issue 15 (1st August 2019) - Lauder, Alexander; Mithani, Suhail; Leversedge, Fraser J.
Abstract : Recalcitrant carpal tunnel syndrome presents a clinical challenge. Potential etiologies of persistent or recurrent symptoms after primary carpal tunnel release include incomplete nerve decompression, secondary sites of nerve compression, unrecognized anatomic variations, irreversible nerve pathology associated with chronic compression neuropathy, perineural adhesions, conditions associated with secondary nerve compression, iatrogenic nerve injury, or inaccurate preoperative diagnosis. Understanding the pertinent surgical anatomy and pathophysiology is essential toward developing an effective diagnostic and treatment strategy. A thorough clinical history and examination guide a comprehensive diagnostic evaluation that includes serial examinations, neurophysiologic testing, and imaging studies. Conservative treatment may provide symptomatic relief; however, surgical management involving revision neuroplasty, neurolysis, nerve reconstruction, and/or local soft-tissue flap augmentation may be indicated in refractory cases.